(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Peña-Santiago, R. Abolafia, J. *2006. Book review: Andrássy, I. 2005. Free-living nematodes of Hungary (Nematoda errantia), I. In: C. Csuzdi & S. Mahunka (Eds.), Pedozoologica Hungarica No. 3. Hungarian Natural History Museum. Budapest, Hungary. 518 pp. [ISBN 963 7093 90 7]